Exploring Vowel Mispronunciation Errors among University Students from West Sumatera - Amna, Shally; Reni, Fetri (JOINT: Journal of Inspirational English Language Teaching, 2024)
Students do a self-introduction every time they start the English class. Although the teachers had given some guidance and explanation, vowel mispronunciation was still present in their speech. The study highlighted the consistent patterns of vowel mispronunciation, explaining the phonological contrast between English and Minangkabau Language and their impact on English learning. The study used a qualitative method to explore 30 Information technology students as data source from West Sumatra who studied at Universitas Putra Indonesia YPTK Padang. The students’ self-introductions are recorded and transcribed to check the errors they make. In addition, a 10-question questionnaire was designed and completed by students to identify the reasons behind their mispronunciation. The research showed that vowel mispronunciation was found in substitution diphthongs with monophthongs and problems with lax, tense, and central vowels. The reasons for these errors are the absence of sound in the student’s native language, the student’s lack of exposure to the English language, and the student’s lack of confidence and motivation. This study suggests that teachers should give extra guidance and practice, so the students will be more aware of their errors, have correct pronunciation models, and have more time to practice and improve their pronunciation.